The effect of needle tip displacement in co-axial electrohydrodynamic processing. Issue 79 (9th August 2016) - Sofokleous, Panagiotis; Lau, Wai K.; Edirisinghe, Mohan; Stride, Eleanor
Abstract : Co-axial electrospraying and electrospinning are versatile electrohydrodynamic (EHD) techniques that can be used to encapsulate a variety of materials in the form of polymeric particles and fibres via a one step process. Abstract : Co-axial electrospraying and electrospinning are versatile electrohydrodynamic (EHD) techniques that can be used to encapsulate a variety of materials in the form of polymeric particles and fibres via a one step process. The successful production of uniform encapsulated products in co-axial EHD (CEHD) processing depends on multiple parameters including solution concentration, applied voltage and needle capillary diameter. Although many studies have been conducted to investigate the effects of these parameters, there has been very limited research on how the axial displacement between the two needle tips affects the final products formed. Hence the purpose of this study was to adjust the positioning of the inner needle such that its tip extends beyond, is level with or resides inside that of the outer needle and to thus determine the most effective arrangement for controlling product size, uniformity and/or yield. Core–shell particles were prepared using two polymers, poly(lactic- co -glycolic)acid (PLGA) as the shell and polymethylsilsesquioxane (PMSQ) as the core and core–shell fibres using PMSQ as the shell and a volatile liquid, perfluorohexane (PFH) as the core. The products formed were analyzed by optical microscopy, scanning electron microscopy (SEM) and transmission electron microscopy (TEM). After analysis, it was concluded that the most effective arrangement for generating both particles and fibres with the optimal combination of size, uniformity and yield was to have the inner needle 2 mm inside the outer needle. This allows for formation of a stable cone–jet and successful encapsulation of the inner liquid within the outer liquid, before the outer stable cone–jet forms. The corresponding collected product diameter and percentage of products in which material was successfully encapsulated were found to be 0.6 ± 0.1 μm and 85 ± 3% respectively for particles and 9 ± 1 μm and 92 ± 2% for fibres.